Environmental awareness and the climate change in students from 5th grade of secondary education - Rojas Avila, Hector (2022)
Of so many problems that humanity must face, environmental degradation is one of them, which generates negative impacts at the local, national and global levels; Therefore, humanity has the responsibility to identify the causes and consequences of different environmental problems, in order to adopt appropriate actions that allow it to mitigate them. For the reasons indicated, the present research seeks to identify in students who are completing the EBR (5th grade of high school) the level of knowledge they have about climate change and its relationship with environmental awareness. For this, the methodology used is the quantitative approach and the population that was part of the study were the students of the I. E. José Carlos Mariátegui La Chira, from the district of San Buenaventura. Finally, the analysis of the results is carried out and the conclusion is reached that there is a regular positive correlation between the two variables raised.